New species of passalus (MITRORHINUS) kaup, 1871 (coleoptera: scarabaeoidea: passalidae) from the extreme west of the brazilian amazon - Oliveira Bevilaqua, Marcus Vinícius; Vasconcelos da Fonseca, Claudio Ruy (Instituto de Ecología, A.C., 2017)
ABSTRACT. Passalus (Mitrorhinus) nodifer sp. nov., from the extreme west of the Brazilian Amazon in the state of Acre is described and illustrated. The new species can be recognized by the head with conspicuous and strong single secondary tubercle; frontal ridges straight and well-marked; mandibles with two apical teeth; aedeagus with parameres reduced with large and rounded apical margin and basal piece with a deep V-shaped notched in the medial region.